PENGARUH EMOTIONAL EXPERIENCE DAN CITRA DESTINASI TERHADAP NIAT BERKUNJUNG KEMBALI MELALUI KEPUASAN WISATAWAN PRINGSEWU RANCH AND RESTO - Aulia Octaviani; Roslina Roslina; Mudji Rachmat Ramelan (Yayasan Nusantara Hasana Berdikari, 2026)
Tourism is one of the industrial sectors currently experiencing growth, evidenced by the surplus of service exports in the Indonesian tourism industry. The tourism sector in Indonesia shows a positive national trend, namely cultural immersion, health and wellness tourism, and eco-tourism, the impact of which is felt by Lampung province. In line with the latest tourism trends, the Pringsewu Ranch and Resto tourist attraction has become one of the destinations that has experienced a positive impact with an increase in the number of visits. This study aims to analyze the influence of emotional experience and destination image on revisit intentions through tourist satisfaction by studying the Pringsewu Ranch and Resto tourist attraction in Pringsewu, Lampung. This study was conducted due to a research gap related to the inconsistency of the influence of destination image on revisit intentions in several previous studies, as well as the still limited research that uses the emotional aspect (emotional experience) of tourist destinations. Data collection for this study was carried out through a questionnaire survey method from 160 respondents using a purposive sampling method. Data analysis was carried out using the PLS-SEM data processing tool. The results of the study indicate that emotional experience and destination image have an influence on revisit intentions both directly and indirectly through the mediating variable, namely tourist satisfaction. This research provides practical insights for the tourism industry in increasing tourist return visits by enhancing tourist satisfaction through enhanced emotional experiences and destination image.